Genomic characterization of Salmonella isolated from retail chicken and humans with diarrhea in Qingdao, China - Wang, Wei; Cui, Jing; Liu, Feng; Hu, Yujie; Li, Fengqin; Zhou, Zhemin; Deng, Xiangyu; Dong, Yinping; Li, Shaoting; Xiao, Jing (Frontiers in Microbiology, 2023)
Salmonella, especially antimicrobial resistant strains, remains one of the leading causes of foodborne bacterial disease. Retail chicken is a major source of human salmonellosis. Here, we investigated the prevalence, antimicrobial resistance (AMR), and genomic characteristics of Salmonella in 88 out of 360 (24.4%) chilled chicken carcasses, together with 86 Salmonella from humans with diarrhea in Qingdao, China in 2020. The most common serotypes were Enteritidis and Typhimurium (including the serotype I 4,[5],12:i:-) among Salmonella from both chicken and humans. The sequence types were consistent with serotypes, with ST11, ST34 and ST19 the most dominantly identified. Resistance to nalidixic acid, ampicillin, tetracycline and chloramphenicol were the top four detected in Salmonella from both chicken and human sources. High multi-drug resistance (MDR) and resistance to third-generation cephalosporins resistance were found in Salmonella from chicken (53.4%) and humans (75.6%). In total, 149 of 174 (85.6%) Salmonella isolates could be categorized into 60 known SNP clusters, with 8 SNP clusters detected in both sources. Furthermore, high prevalence of plasmid replicons and prophages were observed among the studied isolates. A total of 79 antimicrobial resistant genes (ARGs) were found, with aac(6’)-Iaa, blaTEM-1B, tet(A), aph(6)-Id, aph(3’’)-Ib, sul2, floR and qnrS1 being the dominant ARGs. Moreover, nine CTX-M-type ESBL genes and the genes blaNMD-1, mcr-1.1, and mcr-9.1 were detected. The high incidence of MDR Salmonella, especially possessing lots of mobile genetic elements (MGEs) in this study posed a severe risk to food safety and public health, highlighting the importance of improving food hygiene measures to reduce the contamination and transmission of this bacterium. Overall, it is essential to continue monitoring the Salmonella serotypes, implement the necessary prevention and strategic control plans, and conduct an epidemiological surveillance system based on whole-genome sequencing.